Linguistic Sign Oon The Meaning of Sikerei’s Wife’s Tattoos in Madobag Village, South Siberut Mentawai Island - Astuti, Amelia Yuli; Sakaliou, Tuiyak (Fakultas Sastra Universitas Ekasakti, 2024)
This research is entitled